Rwanda : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
This 2004 Article IV Consultation of Rwanda reports that although the recovery in primary activities has been relatively rapid, formal sector activity registered a mixed performance. The expansion of government programs in health, education, water and energy, would widen the structural deficit over the medium term. The shift in the structure of the monetary base could weaken the effectiveness of central bank policy instruments. Rwanda's export base remains highly concentrated and vulnerable to climatic and international price shocks.